2009
DOI: 10.2139/ssrn.1338065
|View full text |Cite
|
Sign up to set email alerts
|

Omitted Variables in the Measure of a Labour Quality Index: The Case of Spain

Abstract: The Working Paper Series seeks to disseminate original research in economics and finance. All papers have been anonymously refereed. By publishing these papers, the Banco de España aims to contribute to economic analysis and, in particular, to knowledge of the Spanish economy and its international environment. The opinions and analyses in the Working Paper Series are the responsibility of the authors and, therefore, do not necessarily coincide with those of the Banco de España or the Eurosystem. The Banco de E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…There are a few other studies that develop an index for the measurement of labour quality growth employing a wage equation approach, i.e. Bolli and Zurlinden (2012) and Lacuesta et al (2011).…”
Section: Overview Of the Dissertationmentioning
confidence: 99%
“…There are a few other studies that develop an index for the measurement of labour quality growth employing a wage equation approach, i.e. Bolli and Zurlinden (2012) and Lacuesta et al (2011).…”
Section: Overview Of the Dissertationmentioning
confidence: 99%
“…Large immigration flows received in the recent past has, at least partly (Banco de España, 2006;Lacuesta et al, forthcoming), contributed to poor productivity performance. Our paper has shown that the initial wage, or productivity, gap between natives and immigrants rapidly decreases as immigrants acquire countryspecific human capital.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we use a simple labour supply and demand framework to investigate several possible explanations for the development of the Spanish wage structure during the period 1995-2010. We first document the importance of distinguishing between changes in the composition of employment and changes in the returns to specific workers' and jobs' characteristics to explain the observed wage evolution.Among the most relevant factors that might imply significant composition effects on the supply side are the educational upgrade of the labour force (see Lacuesta, Puente and Cuadrado, 2010) and huge immigration flows (see Carrasco, Jimeno and Ortega, 2008). 2 On the demand side, major factors include the increasing importance of the construction sector, which leads to an increasing share of low-paid workers (see Gonzalez and Ortega, 2013).…”
Section: Introductionmentioning
confidence: 99%